Stakeholder Consultation Tools: Curriculum Platform Survey for AICCRA Partners - Curtis, Ashley (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This survey supports a key activity of the AICCRA project - development of a curriculum platform, a resource that enables institutions to establish and continually develop curricula that support key competencies/skills in climate services/CSA prioritized by stakeholders in regions. This activity is being led by RUFORUM. However, as part of the AICCRA project, the climate services cluster is supporting some activities related to the platform, including a survey to assess curriculum needs and gaps as identified by AICCRA clusters and partners.